Diferencias clínico-quirúrgicas en pacientes pediátricos sometidos a amigdalectomía por hipertrofia amigdalina frente a amigdalitis recurrente - González Millán, Brenda Gissel (2026)
Objective: To compare the clinical and surgical characteristics among pediatric patients who underwent tonsillectomy for obstructive tonsillar hypertrophy versus recurrent tonsillitis. Materials and methods: An observational, analytical, retrospective cohort study was conducted in patients aged 3–17 years who underwent tonsillectomy between 2019 and 2024 at a tertiary-care hospital. Cases were classified according to the surgical indication. Demographic characteristics, analyzed. Recurrent tonsillitis was defined according to the Paradise criteria. Statistical analysis included the chi-square test and Student’s t-test, with a p value < 0.05 considered statistically significant. Results: A total of 506 patients were included with a mean age of 6.7 years; 58.1 % were male. The most common surgical indication was obstructive tonsillar hypertrophy (78 %), followed by recurrent tonsillitis (22 %). No significant differences were identified between groups regarding demographic characteristics or comorbidities. Operative time was significantly longer in patients with obstructive tonsillar hypertrophy, with a mean duration of 50 min compared to 45 min in the recurrent tonsillitis group (p = 0.028). Mean intraoperative blood loss was higher in the hypertrophy group; however, this difference did not reach statistical significance. The overall complicationrate was 13 % and was higher among patients who underwent surgery for obstructive tonsillar hypertrophy (13.5 % vs. 11.7 %;p = 0.05). The most common complication was postoperative hemorrhage, followed by laryngospasm. Conclusions: Obstructive tonsillar hypertrophy was the most common indication for tonsillectomy in the pediatric population studied and was associated with longer operative times and a slightly higher complication rate. These findings highlight the need for careful postoperative follow-up, particularly in patients undergoing surgery for obstructive indications.